NEW STYLES OF ARABIC LITERARY CRITICISM IN THE ABBASID ERA - Muhammad Hadiyan Ihkam; Nur Illiyin Setya Mufti (Journal of Arabic Literature (JaLi), 2024)
Arabic literary criticism is a manifestation of the efforts of critics to maintain the quality of poetry that contains Arabic values or customs. The Arab literary community during the Abbasid period, namely the critics, became more critical than before. During the Abbasid period, criticism was carried out systematically using certain rules. This is the hallmark of literary criticism during the Abbasid period. This study aims to describe new styles of Arabic literary criticism during the Abbasid period and its development. Researchers use a historical approach. The method used is descriptive qualitative method. The research data was obtained using the library research method. The results of this study indicate that the development of literary criticism during the Abbasid period was caused by the caliph's attention to poets and they received prizes for poetry that were considered good, political disputes between the Abbasid caliphate and the `Alawiyyin group who used poetry as a propaganda tool, and translation and adaptation movements from foreign books. In addition, forms of literary criticism include the issue of plagiarism in Jahili poetry, assessment of the quality of meaning and pronunciation, and comparisons between poems whose superiority is debated.